Outcomes of flexor carpi radialis tendon transfer surgery for patients with radial nerve injury: a comparison of the wide-awake method and general anesthesia - Parviz Ahangar; Hosein Pirmohamadi; Alireza Rahimnia; Mohammad Kazem Emami Meybodi; Mohammad Javanbakht; Mohsen Motalebi; Mehdi Raei; Asghar Yousefi; Seyed Ahmadreza Madinei (European Journal of Translational Myology)
Background: Advanced intraoperative anesthesia techniques have improved patient cooperation, stabilized hemodynamic status, and reduced postoperative pain and disability, especially in reconstructive limb surgeries. The Wide-Awake Local Anesthetic No Tourniquet (WALANT) technique has recently been adopted due to its peculiar advantages, but comparative studies of its benefits and limitations against general anesthesia are not well explored in FCR tendon transfer surgery. This study investigates outcomes of flexor carpi radialis (FCR) tendon transfer surgery in patients with radial nerve injuries using either the Wide-Awake approach or general anesthesia.